Clinical and experimental effects of Nigella sativa and its constituents on respiratory and allergic disorders - Zahra Gholamnezhad; Farzaneh Shakeri; Saiedeh Saadat; Vahideh Ghorani; Mohammad Hossein Boskabady (Mashhad University of Medical Sciences, 2019)
Objective: Black cumin or Nigella sativa (N. sativa) seed has been widely used traditionally as a medicinal natural product because of its therapeutic effects. In this review, the medicinal properties of N. sativa as a healing remedy for the treatment of respiratory and allergic diseases, were evaluated. Material and Methods: Keywords including Nigella sativa, black seed, thymoquinone, respiratory, pulmonary, lung and allergic diseases were searched in medical and nonmedical databases (i.e. PubMed, Science Direct, Scopus, and Google Scholar). Preclinical studies and clinical trials published between 1993 and 2018 were selected. Results: In experimental and clinical studies, antioxidant, immunomodulatory, anti-inflammatory, antihistaminic, antiallergic, antitussive and bronchodilatory properties of N. sativa different extracts, extracts fractions and constituents were demonstrated. Clinical studies also showed bronchodilatory and preventive properties of the plant in asthmatic patients. The extract of N. sativa showed a preventive effect on lung disorders caused by sulfur mustard exposure. The therapeutic effects of the plant and its constituents on various allergic disorders were also demonstrated. Conclusion: Therefore, N. sativa and its constituents may be considered effective remedies for treatment of allergic and obstructive lung diseases as well as other respiratory diseases.